2015
DOI: 10.1002/jcp.25177
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells Differentiating to Adipocytes Accumulate Autophagic Vesicles Instead of Functional Lipid Droplets

Abstract: Adult bone marrow mesenchymal stromal cells (BMSCs) can easily be differentiated into a variety of cells. In vivo transplantation of BMSCs-differentiated cells has had limited success, suggesting that these cells may not be fully compatible with the cells they are intended to replace in vivo. We investigated the structural and functional features of BMSCs-derived adipocytes as compared with adipocytes from adipose tissue, and the structure and functionality of lipid vesicles formed during BMSCs differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…In their studies, mouse models with a targeted deletion of Atg7 exhibited decreased white adipose mass and enhanced insulin sensitivity, while lipid accumulation and protein levels of adipocyte differentiation factors were inhibited. All these results suggested that adipocytic differentiation was attenuated after inhibition of autophagy [7,8], and revealed the phenomenon of the accumulation of autophagic vesicles and intracellular lipid-like vesicles [21]. The results of LC3 and P62 expression in our study (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…In their studies, mouse models with a targeted deletion of Atg7 exhibited decreased white adipose mass and enhanced insulin sensitivity, while lipid accumulation and protein levels of adipocyte differentiation factors were inhibited. All these results suggested that adipocytic differentiation was attenuated after inhibition of autophagy [7,8], and revealed the phenomenon of the accumulation of autophagic vesicles and intracellular lipid-like vesicles [21]. The results of LC3 and P62 expression in our study (Fig.…”
Section: Discussionsupporting
confidence: 65%
“…and indicated increased methionine and FAs levels (and non-detectable creatine) as characteristic of adipogenesis. Subsequent reports employed MS metabolomics, with hBMMSC lipid extracts unveiling changes in free FAs throughout adipogenesis [23,24]. MSC-differentiated preadipocytes (days 5-7) and adipocytes (day 21) lacked specific elongases (possibly hindering endogenous polyunsaturated FA, PUFA, synthesis) and differed from primary adipocytes in decreased levels of LA, -linolenic acid (ALA) and arachidonic acid (AA); and increased docosahexaenoic acid (DHA).…”
Section: Adipogenesismentioning
confidence: 99%
“…The increasing interest in SC lipidomics [8] has resulted in the majority of studies addressing MSCs (mostly using MS [3], along with one report using 1 H NMR [11]), followed by pluripotent SCs [13][14][15] and other SCs [16][17][18]. The main topics studied have comprised MSC differentiation (into adipogenic [19][20][21][22][23], osteogenic [19,[24][25][26][27], or chondrogenic lineages [24,28,29]) and senescence/aging [30][31][32], with most reports employing bone marrow MSCs (BMMSCs) [22,23,[25][26][27][28][29][30]32], followed by adipose tissue-derived MSCs (AMSCs) [19,20,24,[33][34][35][36][37] and other MSCs [11,31]. Initial differentiation studies using GC-MS found that rat BMMSCs exposed to adipogenic media experienced decreases in saturated/unsaturated fatty acid (FAs) ratios over time, while maintaining a fr...…”
Section: Introductionmentioning
confidence: 99%
“…The main topics studied have comprised MSC differentiation (into adipogenic [19][20][21][22][23], osteogenic [19,[24][25][26][27], or chondrogenic lineages [24,28,29]) and senescence/aging [30][31][32], with most reports employing bone marrow MSCs (BMMSCs) [22,23,[25][26][27][28][29][30]32], followed by adipose tissue-derived MSCs (AMSCs) [19,20,24,[33][34][35][36][37] and other MSCs [11,31]. Initial differentiation studies using GC-MS found that rat BMMSCs exposed to adipogenic media experienced decreases in saturated/unsaturated fatty acid (FAs) ratios over time, while maintaining a free fatty acid (FFA) profile similar to that of undifferentiated cells [22,23]. Interestingly, differences between differentiated and primary adipocytes could be partially explained by the lack of essential polyunsaturated fatty acids (PUFAs) in culture media [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation